Altered amygdalar emotion space in borderline personality disorder normalizes following dialectical behaviour therapy - Levine, Seth; Merz, Katharina; Keeser, Daniel; Kunz, Julia I.; Barton, Barbara; Reinhard, Matthias Alexander; Jobst-Heel, Andrea; Padberg, Frank; Neukel, Corinne; Herpertz, Sabine; Bertsch, Katja; Musil, Richard (Journal of psychiatry & neuroscience, 2023)
Background: Borderline personality disorder (BPD) is a mental health condition characterized by an inability to regulate emotions or accurately process the emotional states of others. Previous neuroimaging studies using classical univariate analyses have tied such emotion dysregulation to aberrant activity levels in the amygdala of patients with BPD. However, multivariate analyses have not yet been used to investigate how representational spaces of emotion information may be systematically altered in patients with BPD. - Methods: Patients with BPD performed an emotional face matching task while undergoing MRI before and after a 10-week inpatient program of dialectical behavioural therapy. Representational similarity analysis (RSA) was applied to activity patterns (evoked by angry, fearful, neutral and surprised faces) in the amygdala and temporo-occipital fusiform gyrus of patients with BPD and in the amygdala of healthy controls. - Results: We recruited 15 patients with BPD (8 females, 6 males, 1 transgender male) to participate in the study, and we obtained a neuroimaging data set for 25 healthy controls for a comparative analysis. The RSA of the amygdala revealed a negative bias in the underlying affective space (in that activity patterns evoked by angry, fearful and neutral faces were more similar to each other than to patterns evoked by surprised faces), which normalized after therapy. This bias-to-normalization effect was present neither in activity patterns of the temporo-occipital fusiform gyrus of patients nor in amygdalar activity patterns of healthy controls. - Limitations: Larger samples and additional questionnaires would help to better characterize the association between specific aspects of therapy and changes in the neural representational space. - Conclusion: Our findings suggest a more refined role for the amygdala in the pathological processing of perceived emotions and may provide new diagnostic and prognostic imaging-based markers of emotion dysregulation and personality disorders.Clinical trial registration: DRKS00019821, German Clinical Trials Register (Deutsches Register Klinischer Studien).
Gesehen am 22.01.2024